APPLICATION OF NEURAL NETWORKS IN ARTIFICIAL INTELLIGENCE TASKS - V. F. Antonov; E. A. Pozdnyakov; S. A. Orekhov (Современная наука и инновации)
In recent years, the use of neural networks in information systems has been widely used to solve various classes of problems. This article discusses the basic requirements for the construction of neural networks. An example of constructing a neural network is given on the example ofpattern recognition in access control systems.